Psychological factors influencing the employment of economics-majored northwest minority students in the past two decades - Xinyue Zhang; Mohamad Zuber Abd Majid; Muhammad Hussin (Environment and Social Psychology, 2025)
This study explores the psychological factors affecting the employment of ethnic minority economics majors in Northwest China in the past two decades, filling the gap of the lack of systematic attention to the employment psychology of this group in the existing research. In the context of evolving economic development strategies and education policies for ethnic minorities, despite the key role of the economics profession in regional development, this group still faces unique challenges such as inadequate self-efficacy, limited career expectations, conflicting cultural identities, and employment discrimination. Using a mixed research method, this study is based on 384 questionnaire data and in-depth interviews with 48 respondents, combined with social cognitive career theory, cultural identity model and career adaptability theory, to analyze how psychological factors affect employment choice and career development. The study found that the self-efficacy of minority economics graduates has improved significantly in recent years, and cultural identity plays a positive role in regional employment, but it is still affected by discrimination in the national market. Family support is both a facilitator and may limit occupational mobility. This study not only deepens the understanding of ethnic minority employment psychology, but also provides an empirical basis for universities, governments and enterprises to formulate more targeted employment support policies to promote education equity and regional economic integration.